Metal Complexes for Cancer Sonodynamic Therapy. (8th December 2022) - Mandal, Arif Ali; Kushwaha, Rajesh; Yadav, Ashish Kumar; Banerjee, Samya
Abstract: Sonodynamic therapy (SDT) for cancer treatment is gaining attention owing to its non‐invasive property and ultrasound's (US) deep tissue penetration ability. In SDT, US activates the sonosensitizer at the target deep‐seated tumors to generate reactive oxygen species (ROS), which ultimately damage tumors. However, drawbacks such as insufficient ROS production, aggregation of sonosensitizer, off‐target side effects, etc., of the current organic/nanomaterial‐based sonosensitizers limit the effectiveness of cancer SDT. Very recently, metal complexes with tunable physiochemical properties (such as sonostability, HOMO to LUMO energy gap, ROS generation ability, aqueous solubility, emission, etc.) have been devised as effective sonosensitizers, which could overcome the limitations of organic/nanomaterial‐based sonosensitizers. This concept introduces all the reported metal‐based sonosensitizers and delineates the prospects of metal complexes in cancer sonodynamic therapy. This new concept of metal‐based sonosensitizer can deliver next‐generation cancer drugs. Abstract : Sonodynamic therapy (SDT) is an emerging cancer treatment methodology in which low‐intensity ultrasound activates ultrasound‐active chemical compounds termed sonosensitizers. Recently metal complexes have attracted much attention as new‐generation sonosensitizers due to their tunable energetics. This concept article summarized the current developments in metal‐based SDT. We also provided future outlook on this area of research.